Exploratory study of store image of selected specialty stores : a conceptual perspective. - Tan, Kah Ngee. (2008)
his study examines Singaporean consumers’ perception of local (Bodynits and Projectshop) and foreign (Zara and Espirit) specialty stores in terms of five main store attributes namely, service, presentation, branding, assortment and atmospherics.